Engineer pioneer plants respond to and affect geomorphic constraints similarly along water–terrestrial interfaces world‐wide. Issue 12 (15th September 2015) - Corenblit, Dov; Baas, Andreas; Balke, Thorsten; Bouma, Tjeerd; Fromard, François; Garófano‐Gómez, Virginia; González, Eduardo; Gurnell, Angela M.; Hortobágyi, Borbála; Julien, Frédéric; Kim, Daehyun; Lambs, Luc; et al.
Abstract: Aim: Within fluvial and coastal ecosystems world‐wide, flows of water, wind and sediment generate a shifting landscape mosaic composed of bare substrate and pioneer and mature vegetation successional stages. Pioneer plant species that colonize these ecosystems at the land–water interface have developed specific traits in response to environmental constraints (response traits) and are able to modify habitat conditions by modulating geomorphic processes (effect traits). Changes in the geomorphic environment under the control of engineer plants often feed back to organism traits (feedback traits), and thereby ecosystem functioning, leading to eco‐evolutionary dynamics. Here we explain the joint foundations of fluvial and coastal ecosystems according to feedback between plants and the geomorphic environment. Location: Dynamic fluvial and coastal ecosystems world‐wide. Method: Drawing from a pre‐existing model of 'fluvial biogeomorphic succession', we propose a conceptual framework showing that fluvial and coastal 'biogeomorphic ecosystems' are functionally similar due to eco‐evolutionary feedbacks between plants and geomorphology. Results: The relationships between plant traits and their geomorphic environments within different fluvial and coastal biogeomorphic ecosystems are identified and classified within a framework of biogeomorphic functional similarity according to three criteria: (1) pioneer plants develop specific responses to the geomorphic environment; (2) engineer plants modulate the geomorphic environment; (3) geomorphic changes under biotic control within biogeomorphic ecosystems feed back to organisms. Main conclusions: The conceptual framework of functional similarity proposed here will improve our capacity to analyse, compare, manage and restore fluvial and coastal biogeomorphic ecosystems world‐wide by using the same protocols based on the three criteria and four phases of the biogeomorphic succession model.